2012
DOI: 10.1289/ehp.1104052
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and Asthma-Associated Chemicals in Consumer Products

Abstract: Background: Laboratory and human studies raise concerns about endocrine disruption and asthma resulting from exposure to chemicals in consumer products. Limited labeling or testing information is available to evaluate products as exposure sources.Objectives: We analytically quantified endocrine disruptors and asthma-related chemicals in a range of cosmetics, personal care products, cleaners, sunscreens, and vinyl products. We also evaluated whether product labels provide information that can be used to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
306
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(327 citation statements)
references
References 88 publications
14
306
1
6
Order By: Relevance
“…For many consumer goods, companies are not required to indicate on the label whether these contain EDCs. Moreover, the concentrations may vary greatly among goods of the same type, making it difficult to identify sources of EDCs in the home environment (4,103). Thus, additional direct or on-site observation would be required to identify goods that pose the greatest health risk though exposure.…”
Section: Limiting Error Through Attention To Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For many consumer goods, companies are not required to indicate on the label whether these contain EDCs. Moreover, the concentrations may vary greatly among goods of the same type, making it difficult to identify sources of EDCs in the home environment (4,103). Thus, additional direct or on-site observation would be required to identify goods that pose the greatest health risk though exposure.…”
Section: Limiting Error Through Attention To Questionnaire Designmentioning
confidence: 99%
“…These substances are common additives to household insect repellents, food packaging materials, food storage containers, children's toys, electronics and electric equipment, building and construction materials, paints, furniture, carpets, mattresses, textiles, and personal care products, as shown in Table 1 (4,5). Numerous studies have observed that chemicals contained within household items are released over time into the home environment, and are subsequently detectable in household dust, food and indoor air samples, thus constituting multiple possible pathways of exposure of young children to these chemicals, as described below (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to carcinogenic chemicals is a risk posed by many industrial practices and consumer products. For instance, exposure to chemicals in consumer products, such as cosmetics and even food, is under intense scrutiny from the scientific community (Dodson et al 2012;Johnson 2002;Wagner 2003). An important factor to consider when pursuing regulation or investigation of toxic chemical exposure is the way in which members of the public are made aware of possible exposures and whether they may be able to limit their exposure due to lifestyle changes.…”
Section: Chemical Usementioning
confidence: 99%
“…İçeriklerinde etken maddelerin yanı sıra koruyucular, parfümler gibi çok farklı kimyasallar; fitalatlar ve diğer yumuşatıcılar, bisfenol A, parabenler, benzofenonlar (ultraviyole filtresi), polisiklikmiskler, triklosan (antimikrobiyal), dioksan, organik çözücüler, pigmentler, formaldehit, ağır metaller, koruyucular ve etkinliği ve etki süresini artıracak diğer katkılar vardır (2)(3)(4)(5). Çalışmalar kozmetiklerin çevresel kimyasallara en önemli maruziyet kaynaklarından biri olduğunu ortaya koymaktadır (6).…”
Section: Introductionunclassified